Religiöse Individualisierung in historischer Perspektive Abschlussbericht für die zweite Förderphase der Kolleg-Forschungsgruppe 1013/Final Report of the Kolleg-Forschungsgruppe 1013 for the Second Funding Period 2013-2018 - Suitner, Riccarda; Mulsow, Martin; Rüpke, Jörg (De Gruyter, 2020)
This volume provides access to the working and results of six years of research on religious individualisation. It demonstrates the independence of individualisation and modernisation. It has proved that religion is a motor of individualisation. And it has proved that the wide range of phenomena under the umbrella term of 'individualisation' are to be found in many premodern societies, in India for instance as much as in Europe.